Metallicities of Globular Clusters m3 and m5 from VI CCD Photometry - Young-Jong Sohn; Hyun-Chul Lee (Journal of Astronomy and Space Sciences, 2000)
To derive the metallicities of M3 and M5, we used the shape of red giant branch, horizontal branch magnitude, and red giant branch bump on the (V - I) - V color magnitude diagrams. [Fe/H] values ranging -1.46 -1.69 for M3, and -1.00 -1.49 for M5 are estimated. This result leads the morpholgies of red giant and horizontal branches on the (V-I) - v color magnitude diagrams can be good indirect metallicity indicators of galactic globular clusters.